Muslim Women Emancipation Discourse: Analyzing the Legal Thoughts of Muhammad Quraish Shihab - Aibak, Kutbuddin (Ulumuna, 2023)
This article aims to analyze several issues on women in Muhammad Quraish Shihab's fatwās (legal opinions) contained in several of his works in the form of questions and answers. This study departs from the existing studies on Muslim women's emancipation movements, particularly which have become a common trend in the modern Muslim world, including in Indonesia. Shihab's thoughts on Muslim women are worth studying because he attempts to unravel the primary Islamic religious texts that deal with women's issues within their initial context to provide religious instructions for Muslim women today without necessarily renouncing the traditional methods of reasoning. This article argues that Shihab's articulation of Indonesian women's fiqh (jurisprudence) using exegetical logic opens a broader space and provides an alternative for more emancipatory interpretations of religious texts operating within the grand corridor of Islamic religious and intellectual tradition.